Integration of Knowledge, Institutional Strengthening, and Academic Collaboration: An Institutional Visit Study at UIN Alauddin Makassar - Dadan Rusmana; Wiryo Wiryo; Mohammad Taufiq Rahman; Andi Muhammad Ali Amiruddin (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to analyze the contribution of an academic visit conducted by the Scientific Consortium of UIN Sunan Gunung Djati Bandung to the strengthening of knowledge integration, institutional development, and academic collaboration at UIN Alauddin Makassar. Key concepts employed in this study include knowledge integration, higher education benchmarking, epistemic networking, and Islamic higher education governance. This research adopts a qualitative case study approach, utilizing field observations, focus group discussions, limited interviews, and institutional document analysis. The scope of the study covers the Faculty of Ushuluddin, the Institute for Research and Community Service (LP2M), and the Faculty of Medicine and Health Sciences (FKIK) at UIN Alauddin Makassar. The findings reveal that knowledge integration at UIN Alauddin Makassar has moved beyond conceptual formulation toward institutionalization, as reflected in integrative curricula, research governance, laboratory development, and value-based professional education. Academic visits function as an effective mechanism for institutional learning and epistemic reflection, fostering the consolidation of integrative paradigms and strategic institutional development within Islamic higher education. Key challenges include limitations in research infrastructure, disparities in human resource capacity, and the rigidity of national accreditation and professional standards. This study recommends strengthening inter-institutional research collaboration, developing sustainable benchmarking models, and deepening governance-based knowledge integration. This study contributes empirically to the literature on knowledge integration in Islamic higher education by demonstrating how integrative paradigms are operationalized through institutional policies, academic practices, and benchmarking-based collaboration.